اليمين غير القضائية - حسن نزار (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The oath is two types ,judicial and extrajudicial , judicial oath is decisive Oath and Complementary oath , extrajudicial oath is an oath which can be taken or you could agree to do it out of court . The majority of jurists and the court of cassation in Syria and Egypt are accepted the legal existence of extrajudicial oath, and they considered it as " conventional decisive Oath " , and we are going to discuss probative legal value to this oath, according to the Syrian law of evidence , and knowing the system which adopted this Law in organizing means of proof ,and determined the legal value to the special agreements of the means of proof ,and after searching we had a result which is contrary to which public jurists and jurisprudence adopted. The result is the illegality to the extrajudicial oath as a mean of proof which is dependent by itself , however we can consider it as a judicial presumption , that the court is free to take it or leave it . اليمين نوعان قضائية وغير قضائية ، واليمين القضائية حاسمة ومتممة ، أما اليمين غير القضائية فهي اليمين التي تؤدى أو يُتفق على تأديتها في غير مجلس القضاء. أقر أغلب الفقهاء و قضاء محكمتي النقض في سورية ومصر الوجود القانوني لليمين غير القضائية، واعتبروها من قبيل " اليمين الحاسمة الاتفاقية"، و سنعمد في هذا البحث إلى تبين القيمة القانونية الإثباتية لهذه اليمين، في ضوء نصوص قانون البينات السوري، ومعرفة المذهب الذي تبناه هذا القانون في تنظيم طرق الإثبات،وتحديد حكم الاتفاقات الخاصة بطرق الإثبات، ووصلنا بعد البحث إلى نتيجة مخالفة لما استقر عليه عامة الفقه والاجتهاد القضائي وهي عدم قانونية اليمين غير القضائية كطريقة إثبات مستقلة بذاتها، ولكن يمكن اعتبارها قرينة قضائية يعود تقديرها لقاضي الموضوع.